Analysis of Production Labor Costs of Aswaja Pekalongan Batik Convection Companies - Zam’ul Haq, M. Rosyid Mahfudz; Mulyadi, Dedi; Sandi, Santi Pertiwi Hari (Jurnal Ilmiah Wahana Pendidikan, 2025)
Income is revenue obtained through the results of economic activities related to sales activities of production factors owned by a company. As is known in the theory of production factors, the quantity of output related to income directly depends on the number of workersin a company. In increasing production which is supported by efficient resources and runs systematically, appropriate income can be obtained from the number of workers. This research was conducted with the aim of analyzing the number of workers in increasing income at the Aswaja Pekalongan Batik Convection. The type of research used is quantitative descriptive. The results of this research show that the Pekalongan Aswaja Batik Convection has experienced an increase in workforce since the start of the year 2018 business until now of the year 2024, after the addition of workforce the Pekalongan Aswaja Btik Convection has experienced an increase in the income earned by 64%.